Mercado bursátil en Colombia (2022)
The Colombian stock market has evolved over time, offering new investment opportunities for legal entities and individuals. However, challenges such as lack of knowledge and distrust persist, limiting the active participation of Colombians. The objective of this paper is to analyze the advantages of the stock and foreign exchange market in Colombia, focusing on individuals and legal entities.